Recruitment of heads of municipalities: cross-regional variability in the choiceof institutional design - Panov, P.V. (Perm Federal Research Centre Journal, 2018)
The transformation of the local government institutional structure in Russia over the last decade is examined from the view of the theory of «principal-agent» interactions. Governors as «principals» consider heads of municipalities as their «agents» and, therefore, are interested in having impact on their recruitment. In 2014-2015 when the regional authorities got powers to determine the institutional structure of local government, a new «contest model», which increases the infl of governors on the selection of the heads, was introduced. However, in spite of the fact that this model is becoming more widespread in Russia in general, there are signifi cross-regional differences. Comparative analysis shows that the model of elected heads of municipalities has more chances to survive in those subjects of the Russian Federation, where the regional government (a) controls the regional elites and political processes to lesser extent and (b) the local communities have greater fi resources. At the same time, statistically these dependencies are rather weak, therefore, the institutional choice is dictated by situational factors rather than long-term tendencies.